Non-contact electro capacitive cancer therapy (ECCT) modulate the mRNA expression of p53, Apaf-1, survivin, NF-κB, TSP-1 and bFGF in DMBA-induced breast cancer rat - Hidayah, Nurul; Putra, Agung; Alamsyah, Firman; Pratiwi, Rarastoeti (Published by Universitas Gadjah Mada, 2026)
Breast cancer is the most common cancer that causes death in women in the world. Cancer development is facilitated by the inhibition of apoptosis and induction of angiogenesis. Current cancer therapy still encounters problems in the form of recurrence, resistance, and side effects of drugs. Non-contact static electric field therapy, electro capacity cancer therapy (ECCT) with medium frequency, is a therapy developed to inhibit the proliferation of tumor cells. This study aimed to determine the mRNA expression of p53, Apaf-1, survivin related to apoptosis and NF-κB, bFGF and TSP-1 related to angiogenesis in rat breast tumor tissue after ECCT frequency of 150 kHz. Breast tissue samples and rat breast tumor nodules stored in RNA later at -20°C were used. The tissue was obtained from the non-induction non-therapy (NINT) group, induction non-therapy (INT), non-induction therapy (NIT), and induction therapy (IT). mRNA expression of p53, Apaf-1, NF-κB, bFGF and TSP-1 were analyzed using qRT-PCR and calculated with the Livak formula. Data were analyzed using one-way Anova and post-hoc LSD. The results showed that, mRNA expression of p53, Apaf-1 and TSP-1 in the IT group increased significantly, and mRNA expression of survivin and bFGF decreased significantly compared to the INT group. However, the expression of NF-κB mRNA in the IT group remained the same as in the INT group. In conclusion, ECCT with a frequency of 150 kHz upregulates p53, Apaf-1 and TSP-1 mRNA expression and downregulates survivin and bFGF mRNA expression but have no effect on NF-κB mRNA expression in rat breast tumor tissue.